Bioinformatics and Expression Analysis of PAL Gene Family of Poplar Plant under Different Nitrogen Treatments - C. J. Yang，M. Jin; Y. Q. Zhang，Y. B. Duan (Journal of Animal and Plant Sciences, 2023)
Phenylalanineammonia lyase is the crucial enzyme and rate-limiting enzyme in the biosynthesis pathway of phenylpropane. Lignin, phytoalexin and many kinds of active substances produced in this pathway, such as flavonoids and phenols, play a key role in lignification, stress resistance, insect resistance and disease resistance of plant cells. In this study, five PAL gene sequences ofPopulus simonii × p.nigra were studied, and the basic characteristics of their genes and proteins were analyzed. The tissue expression pattern of PAL gene of Populus simonii × p.nigra were tested by real-time quantitative. PCR under different nitrogen forms and nitrogen concentrations. The results showed that the physicochemical property of five proteins were similar. All the proteins except PtrPAL4 and PtrPAL5 were stained on chromosome 10, PtrPAL1, PtrPAL2 and PtrPAL3 were on chromosome 6, 8 and 16, respectively. The five proteins were mainly distributed in chloroplasts, and the three-level structures of the five proteins were consistent, and they were all homologous tetramers. The evolutionary relationship results show that the PAL gene of poplar is highly homologous to rice and Arabidopsis. When poplar was treated with 0.1 mmol · L-1, 10 mmol · L-1 and 2 mmol · L-1, the relative expression of PAL genes in stem was the highest under low nitrogen level, and was most obviously induced by ammonium nitrogen.
Keywords: Poplar; PAL gene family; bioinformatics; Stem; Gene expression